Gustav Nikolaus Specht (1860–1940): His impact on Kraepelin’s nosology and approaches to his position in National Socialism Gustav Nikolaus Specht (1860–1940): Sein Einfluss auf die Nosologie Kraepelins und Annäherungen an seine Position im Nationalsozialismus - Braun, Birgit; Kornhuber, Johannes (Der Nervenarzt, 2021)
Introduction: Gustav Specht (1860–1940) represents the beginning of the university psychiatry in Erlangen. 80 years after his death, this article focuses on Specht’s role in the psychopathologic nosological discussion initiated by Kraepelin. Despite the sparse data situation, the authors approach for the first time Specht’s position within psychiatry under National Socialism. Methods: The relevant primary and secondary literature as well as archival sources were evaluated. Results: In 1897 Specht was appointed supernumerary professor and in 1903 the first full professor for psychiatry in Erlangen. Specht elaborated the role of the manic element in paranoia. Specht added the depressive reaction to Bonhoeffers “exogenic reaction type” in 1913; Specht himself was in the view of some colleagues suspected of having a cyclothyme temperament and twice suffered from exogenous depressive reaction. Discussion: Specht’s research studies on the pathological affect in chronic paranoia influenced the contemporary psychopathological discussion in a sustainable manner. Specht’s change of attitude towards eugenic measures can be interpreted as an adaptation to the National Socialist regime. Conclusion: The work of Gustav Specht can stimulate the cultivation of an interdisciplinary psychopathological discourse.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Chronic mania; Contemporary psychopathological discussion; Exogenous depressive reaction; Hereditary health; Paranoia